Effect of processed spent bleaching earth on compressive strength and tensile splitting strength of foamed concrete - Mohd Shariff, Razak (2018)
Foamed concrete is a kind of lightweight concrete that has good workability and does not require compaction process. Generally, it recognizes foaming concrete as building materials with low strengths and weaknesses, especially when the building materials are subject to high impact energy. However, foaming concrete is a potential material for building futuristic concepts. Futuristic construction is a light, economical and easy building construction and most importantly is environmentally friendly. In this study, cement was replaced by Spent Bleaching Earth Processing (PSBE) in a certain percentage of concrete to assess its strengths. Percentage of PSBE percentage used is 10%, 20% and 30% with foam density 1600kg / m3. To determine the value of the compressive strength and the value of tensile splitting strength of the experimental pressure tensile, 36 cube and 36 cylinder samples was prepared. Compression testing and tensile splitting test was performed on the sample for 28, 60, and 90 days curing age. It has been specified that the strength of foamed concrete using PSBE as partial cement replacement clearly increased with the increase of the percentage of PSBE as cement replacement. Result exhibit that 30% PSBE as partial cement replacement shows the highest strength which is 16.08 MPa for compressive test and 17.46 MPa for tensile splitting test. Overall, the major findings for both experiments show that increment of PSBE percentage increase the foamed concrete strength.